Modified iron-based biochar composite material, preparation method and application of modified iron-based biochar composite material in anaerobic engineering for rapidly recovering seriously acidified kitchen waste
Through the preparation of modified iron-based biochar composite materials, the problem of rapid recovery of the anaerobic system of kitchen waste is solved, the rapid recovery and stable operation of anaerobic projects are achieved, and environmental protection problems and high disposal costs are avoided.
Patent Information
- Application Number
- CN202411439775.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-10-15
AI Technical Summary
The existing technology cannot quickly restore the seriously acidified anaerobic system of kitchen waste without stopping production, resulting in huge losses and environmental protection problems in kitchen waste disposal projects.
The modified iron-based biochar composite is prepared by low-temperature carbonization, activation, co-precipitation and in-situ polymerization reactions to improve the specific surface area and conductivity of biochar and is used to quickly restore the acidification state in anaerobic engineering.
It has achieved rapid recovery of the anaerobic system without stopping production, shortened construction period, avoided the disposal of acidified liquid, improved the economic value of biogas, and maintained stable operating conditions in the anaerobic tank.
Smart Images

Figure CN119218994A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of anaerobic digestion, and in particular to a modified iron-based biochar composite material, a preparation method and application thereof in an anaerobic engineering for rapidly recovering severely acidified kitchen waste. Background Art
[0002] Anaerobic digestion is one of the best technical ways to reduce environmental pollution from biomass waste and recycle the clean energy contained in it. Organic solid waste such as organic waste has a high organic matter content and a high water content. Anaerobic digestion of organic waste has the advantages of low energy consumption, small footprint, and the ability to reduce secondary pollution. However, acidification is very likely to occur in the anaerobic process of food waste. High salt, too fast acidification during hydrolysis, many pathogens, low C / N, high alkalinity during fermentation, single functional microbial species, unbalanced nutrients, overload operation, serious deviations in operating control conditions such as pH and temperature, and the influx of toxic substances are all causes of anaerobic acidification of food waste.
[0003] At present, the anaerobic system that has been acidified mainly relies on stopping feeding, cleaning the tank, and re-inoculating and cultivating. However, this process is very slow. It often takes more than three or four months from stopping feeding to returning to normal daily feeding before acidification, and the disposal of acidified materials also faces environmental issues. This has caused huge losses to the operating food waste treatment projects and has a bad social impact. Therefore, a rapid recovery method for severely acidified food waste without stopping production is urgently needed. Summary of the invention
[0004] In view of the shortcomings of the prior art mentioned above, the object of the present invention is to provide a modified iron-based biochar composite material to solve the problem in the prior art that it is impossible to achieve rapid recovery of severely acidified anaerobic systems without stopping production. At the same time, the present invention will also provide a method for preparing the modified iron-based biochar composite material; in addition, the present invention will also provide the application of the modified iron-based biochar composite material in the rapid recovery of severely acidified kitchen waste anaerobic engineering.
[0005] In order to achieve the above-mentioned object and other related objects, the present invention provides the following technical solutions: The first aspect of the present invention provides a method for preparing a modified iron-based biochar composite material, comprising the following steps: S1. Using lignocellulose-rich biomass as raw material, the crushed raw material is subjected to low-temperature carbonization treatment in an oxygen-deficient environment to obtain pre-oxidized biochar; S2, activating the pre-oxidized biochar to obtain activated biochar; S3, modifying the iron-based material onto the surface of the activated biochar by a co-precipitation method to obtain iron-based biochar; S4, dissolving the conductive polymer monomer in a solvent, uniformly dispersing the iron-based biochar in the conductive polymer monomer solution, heating the mixed solution to cause an in-situ polymerization reaction, thereby coating the conductive polymer on the surface of the iron-based biochar; S5. After the reaction is completed, the product is separated, washed and dried to obtain the modified iron-based biochar composite material.
[0006] The preferred solution of step S1 is as follows: The lignocellulose-rich biomass is selected from at least one of sawdust, bamboo, fruit shell, rice shell, and coconut shell. These biomass raw materials contain rich organic components, are easy to form a porous structure, and have a wide source and low cost.
[0007] The particle size of the raw material after crushing is between 80 mesh and 120 mesh. Preferably, the particle size of the raw material after crushing is 100 mesh.
[0008] The temperature of low-temperature carbonization is between 300 and 500°C, and the time of low-temperature carbonization is between 0.5 and 1 hour.
[0009] The preferred solution of step S2 is as follows: The activation treatment process includes: mixing the pre-oxidized biochar with an activator solution, heating and reacting for a period of time, and separating, washing and drying after the reaction to obtain activated biochar.
[0010] The activator is selected from phosphoric acid or sulfuric acid. After the activation reaction, the porosity and specific surface area of the biochar can be increased, which can not only enhance the ability of the biochar to adsorb VFA, but also ensure that the iron ions are fully loaded onto the surface and pores of the biochar, improve the conductive network of the iron ions, and achieve more efficient electron transfer.
[0011] The activation temperature is between 400~600℃, and the activation time is between 1~2h.
[0012] The preferred solution of step S3 is as follows: The iron-based materials include ferric chloride (FeCl3) and ferrous sulfate (FeSO4).
[0013] The co-precipitation modification process includes: dissolving FeCl3·6H2O and FeSO4·7H2O in water to prepare a mixed iron salt solution, fully immersing the activated biochar in the iron salt solution, heating and adjusting the pH during stirring to allow the iron salt to undergo a co-precipitation reaction, and separating, washing, and drying after the reaction to obtain iron-based biochar.
[0014] The temperature of the coprecipitation reaction is between 60 and 80°C, and the pH of the coprecipitation reaction is between 8.5 and 10.
[0015] The molar ratio of FeCl3 to FeSO4 is between 2:1 and 1:2; preferably (1 to 1.5):1.
[0016] During the co-precipitation reaction, iron oxides are precipitated on the surface of biochar, which can enhance its catalytic, adsorption and conductivity functions. The co-precipitation method has simple operating steps and is suitable for industrial production.
[0017] The preferred solution of step S4 is as follows: The conductive polymer is selected from at least one of polyaniline, polypyrrole, polythiophene and polyethylene dioxythiophene. Correspondingly, the conductive polymer monomer is selected from at least one of aniline, pyrrole, thiophene and ethylene dioxythiophene.
[0018] The solvent is selected from water, alcohols, ketones or ethers.
[0019] An oxidant is also added during the in-situ polymerization reaction, and the oxidant includes at least one of persulfate and chlorate. Preferably, the oxidant is selected from at least one of ammonium persulfate, sodium persulfate, sodium chlorate, and potassium chlorate. More preferably, the amount of persulfate added is equivalent to 0.5-5% of the amount of conductive polymer monomer added, and the amount of chlorate added is equivalent to 0.1-1% of the amount of conductive polymer monomer added.
[0020] The temperature of the in-situ polymerization reaction is between 60 and 120° C., and the time of the in-situ polymerization reaction is between 12 and 36 hours.
[0021] An acidic solution needs to be added to the mixed solution to adjust the pH to acidic; preferably, the pH is adjusted to 3-5.
[0022] The modified iron-based biochar composite material prepared by the present invention not only has a high specific surface area and a porous structure, but can also effectively adsorb VFA, thereby reducing the concentration of VFA in the tank; moreover, electron transfer can be achieved through the redox reaction of iron ions, which independently participates in the biomethanization process of organic matter and accelerates the conversion of VFA; in addition, by coating the surface of the iron-based biochar with a conductive polymer, the overall conductivity and electron transfer efficiency can be significantly improved, serving as a more efficient electron transfer method.
[0023] A second aspect of the present invention provides a modified iron-based biochar composite material, which is prepared by the above-mentioned preparation method.
[0024] The third aspect of the present invention provides an application method of a modified iron-based biochar composite material in an anaerobic project for rapid recovery of severely acidified food waste.
[0025] The modified iron-based biochar composite material is added into the severely acidified anaerobic tank, and the added amount of the modified iron-based biochar composite material is 0.5 to 10.000 of the total amount in the tank.
[0026] The application method specifically comprises the following steps: (1) A modified iron-based biochar composite material is added into a severely acidified anaerobic tank using a dosing device, wherein the initial start-up amount of the modified iron-based biochar composite material is added at 0.5% of the amount of slurry in the tank; (2) Resume feeding, when the organic load changes from 0kg VS / m 3 Up to 0.5kg VS / m 3 In the stage, the daily feed amount increased by 15% compared with the previous day, and the daily dosage of the modified iron-based biochar composite material was feed amount (t / d)*TS content (%)*5%; (3) When the organic load increases from 0.5 kg VS / m 3 Up to 1.0kg VS / m 3 In the first stage, the daily feed amount increased by 10% compared with the previous day, and the daily dosage of the modified iron-based biochar composite material was feed amount (t / d)*TS content (%)*4%; (4) When the organic load increases from 1.0 kg VS / m 3 Up to 2.0kg VS / m 3 In the first stage, the daily feed amount increased by 5% compared with the previous day, and the daily dosage of the modified iron-based biochar composite material was feed amount (t / d)*TS content (%)*3%; (5) When the organic load increases from 2.0 kg VS / m 3 Up to 3.0kg VS / m 3 In the first stage, the daily feed amount increased by 3% compared with the previous day, and the daily dosage of the modified iron-based biochar composite material was feed amount (t / d)*TS content (%)*2%; (6) When the organic load reaches 3.0 kg VS / m 3 , feed normally every day and stop adding modified iron-based biochar composite materials.
[0027] Among them, daily feed index testing: feed amount, TS (total suspended solids), VS (volatile solids), and pH.
[0028] In step (2), after the feed is resumed, the feed rate is increased starting from 1 t / d.
[0029] Furthermore, the process of step (2) lasts for 7 days, the process of step (3) lasts from the 8th day to the 15th day, the process of step (4) lasts from the 16th day to the 29th day, and the process of step (5) lasts from the 30th day to the 42nd day.
[0030] During the application process, there is no need to stop production, and the feed can be directly fed after adding iron-based biochar. With the help of modified iron-based biochar composite materials, the daily feed load can be quickly increased to reach full production as soon as possible; and it can recover from severe acidification to full production within 45 days, which shortens the construction period by 45 days or more than the traditional method of cleaning the tank first and then inoculating and cultivating.
[0031] Since the modified iron-based biochar composite material is used to rescue the acidified anaerobic tank, there is no need to clean the tank, there is no problem of disposing the acidified liquid, and environmental problems and high disposal costs are avoided. The modified iron-based biochar composite material is used to rescue the acidified anaerobic tank. It is not a simple physical and chemical action, but a stable microbial system is constructed. The pH, VFA, TAC (total alkalinity), TS, VS, COD (chemical oxygen demand), ammonia nitrogen, and biogas components in the anaerobic tank remain stable. During the acidification recovery period and for a period of time after the recovery, the methane content in the biogas is significantly higher than the value before acidification, which is conducive to improving the economic value of the biogas.
[0032] Furthermore, a stirrer is installed in the anaerobic tank, and the stirring of the stirrer can balance the temperature in the tank, and the temperature fluctuation in the anaerobic tank does not exceed 1°C.
[0033] Furthermore, the anaerobic tank is equipped with a liquid level meter, a temperature sensor, a pressure sensor, a biogas flow meter, a gas analyzer and a pH meter. Through these detection instruments, the pH, VFA, TAC (total alkalinity), TS, VS, COD (chemical oxygen demand), ammonia nitrogen and biogas components in the anaerobic tank can be monitored in real time to keep them stable, which provides another guarantee for judging whether the acidification system has returned to normal.
[0034] As described above, the modified iron-based biochar composite material, preparation method and application thereof in the rapid recovery of severely acidified kitchen waste anaerobic engineering of the present invention have the following beneficial effects: In the process of preparing the modified iron-based biochar composite material, the present invention uses activation treatment to make the biochar have a higher specific surface area and porous structure, improve its adsorption capacity, and be able to dope more iron elements to promote electron transfer, and strengthen the electron transfer process between acid-producing bacteria and methanogens; in addition, by coating the surface of the iron-based biochar with a conductive polymer, the overall conductivity and electron transfer efficiency of the material can be significantly improved, the electron transfer network between acid-producing bacteria and methanogens can be improved, and the anaerobic digestion efficiency can be greatly improved, so that the anaerobic system of severely acidified food waste can be quickly restored. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 Shown is a schematic diagram of the structure of the anaerobic tank disclosed in the present invention.
[0036] Figure numerals: 1. anaerobic tank; 2. liquid level meter; 3. temperature sensor; 4. agitator; 5. pressure sensor; 6. biogas flow meter; 7. biogas gas analyzer; 8. dosing device; 9. pH meter. DETAILED DESCRIPTION
[0037] The following is a description of the implementation of the present invention by means of specific embodiments. Those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification.
[0038] Example 1 A modified iron-based biochar composite material is obtained by the following preparation method: S1. Sawdust from a wood processing plant was crushed through a 100-mesh sieve and carbonized at 400°C for 1 h in an oxygen-deficient environment to obtain pre-oxidized biochar; S2, putting the pre-oxidized biochar into a 30% concentration phosphoric acid solution, and performing activation reaction at 500°C for 1 hour to obtain activated biochar; S3, dissolving FeCl3·6H2O and FeSO4·7H2O in water to prepare iron salt solutions with concentrations of 0.08M and 0.1M respectively, mixing the two, and fully immersing the activated biochar in the mixed iron salt solution. During the stirring process, the temperature is raised to 70°C and sodium hydroxide is added to adjust the pH to 9 to allow the iron salt to co-precipitate. The reaction is carried out for 2 hours. After the reaction is completed, the biochar is separated, washed, and dried to obtain iron-based biochar; S4, dissolving 200 μL of pyrrole in 500 mL of water, taking 15 g of the iron-based biochar prepared above and evenly dispersing it in the pyrrole solution, adding hydrochloric acid to adjust the pH to 5, and adding 50 μL of 10% ammonium persulfate solution, mixing evenly, and then heating the mixed solution to 80°C to allow in-situ polymerization to occur for 12 hours, thereby coating the surface of the iron-based biochar with polypyrrole; S5. After the reaction is completed, the product is separated by centrifugation, washed with deionized water and anhydrous ethanol in turn, and dried in an oven at 80° C. for 24 hours to obtain the modified iron-based biochar composite material.
[0039] Example 2 A modified iron-based biochar composite material is obtained by the following preparation method: S1. Sawdust from a wood processing plant was crushed through a 100-mesh sieve and carbonized at 400°C for 1 h in an oxygen-deficient environment to obtain pre-oxidized biochar; S2, putting the pre-oxidized biochar into a 30% concentration phosphoric acid solution, and performing activation reaction at 500°C for 1 hour to obtain activated biochar; S3, dissolving FeCl3·6H2O and FeSO4·7H2O in water to prepare iron salt solutions with concentrations of 0.08M and 0.1M respectively, mixing the two, and fully immersing the activated biochar in the mixed iron salt solution. During the stirring process, the temperature is raised to 70°C and sodium hydroxide is added to adjust the pH to 9 to allow the iron salt to co-precipitate. The reaction is carried out for 2 hours. After the reaction is completed, the biochar is separated, washed, and dried to obtain iron-based biochar; S4, dissolving 200 μL of aniline in 500 mL of water, taking 15 g of the iron-based biochar prepared above and evenly dispersing it in the aniline solution, adding hydrochloric acid to adjust the pH to 3, and adding 10 μL of 10% ammonium persulfate solution, mixing evenly, and then heating the mixed solution to 80°C, and in-situ polymerization for 12 hours, thereby coating the surface of the iron-based biochar with polyaniline; S5. After the reaction is completed, the product is separated by centrifugation, washed with deionized water and anhydrous ethanol in turn, and dried in an oven at 80° C. for 24 hours to obtain the modified iron-based biochar composite material.
[0040] Example 3 A modified iron-based biochar composite material is obtained by the following preparation method: S1. Grind the coconut shell through a 100-mesh sieve, and perform low-temperature carbonization at 400°C for 1 h in an oxygen-deficient environment to obtain pre-oxidized biochar; S2, putting the pre-oxidized biochar into a 30% concentration phosphoric acid solution, and performing activation reaction at 500°C for 1 hour to obtain activated biochar; S3, dissolving FeCl3·6H2O and FeSO4·7H2O in water to prepare iron salt solutions with concentrations of 0.1M and 0.1M respectively, mixing the two, and fully immersing the activated biochar in the mixed iron salt solution. During the stirring process, the temperature is raised to 70°C and sodium hydroxide is added to adjust the pH to 9 to allow the iron salt to co-precipitate. The reaction is carried out for 2 hours. After the reaction is completed, the biochar is separated, washed, and dried to obtain iron-based biochar; S4, dissolving 200 μL of thiophene in 500 mL of water, adding 0.001 g of sodium chlorate, mixing evenly, taking 15 g of the iron-based biochar prepared above and evenly dispersing it in the pyrrole solution, adding hydrochloric acid to adjust the pH to 3, and then heating the mixed solution to 100 ° C, and in situ polymerization for 12 hours, thereby coating the surface of the iron-based biochar with polythiophene; S5. After the reaction is completed, the product is separated by centrifugation, washed with deionized water and anhydrous ethanol in turn, and dried in an oven at 60° C. for 24 hours to obtain the modified iron-based biochar composite material.
[0041] Example 4 A modified iron-based biochar composite material is obtained by the following preparation method: S1. The bamboo was crushed through a 100-mesh sieve and carbonized at 400°C for 1 h in an oxygen-deficient environment to obtain pre-oxidized biochar; S2, putting the pre-oxidized biochar into a 30% concentration phosphoric acid solution, and performing activation reaction at 500°C for 1 hour to obtain activated biochar; S3, dissolving FeCl3·6H2O and FeSO4·7H2O in water to prepare iron salt solutions with concentrations of 0.08M and 0.1M respectively, mixing the two, and fully immersing the activated biochar in the mixed iron salt solution. During the stirring process, the temperature is raised to 70°C and sodium hydroxide is added to adjust the pH to 9 to allow the iron salt to co-precipitate. The reaction is carried out for 2 hours. After the reaction is completed, the biochar is separated, washed, and dried to obtain iron-based biochar; S4, dissolving 300 μL of ethylenedioxythiophene (EDOT) in 500 mL of water, taking 15 g of the iron-based biochar prepared above and evenly dispersing it in the aniline solution, adding hydrochloric acid to adjust the pH to 5, and adding 20 μL of 10% ammonium persulfate solution, mixing evenly, and then heating the mixed solution to 80°C, and in-situ polymerization for 24 hours, so as to coat the surface of the iron-based biochar with polyaniline; S5. After the reaction is completed, the product is separated by centrifugation, washed with deionized water and anhydrous ethanol in turn, and dried in an oven at 80° C. for 24 hours to obtain the modified iron-based biochar composite material.
[0042] Comparative Example 1 An iron-based biochar is obtained by the following preparation method: S1. Sawdust from a wood processing plant was crushed through a 100-mesh sieve and carbonized at 400°C for 1 h in an oxygen-deficient environment to obtain pre-oxidized biochar; S2, putting the pre-oxidized biochar into a 30% concentration phosphoric acid solution, and performing activation reaction at 500°C for 1 hour to obtain activated biochar; S3. Dissolve FeCl3·6H2O and FeSO4·7H2O in water to prepare iron salt solutions with concentrations of 0.08M and 0.1M respectively, mix the two, and fully immerse the activated biochar in the mixed iron salt solution. During the stirring process, raise the temperature to 70°C and add sodium hydroxide to adjust the pH to 9 to allow the iron salt to co-precipitate. React for 2 hours. After the reaction, separate, wash and dry the biochar to obtain iron-based biochar.
[0043] Comparative Example 2 An iron-based biochar is obtained by the following preparation method: S1. Sawdust from a wood processing plant was crushed through a 100-mesh sieve and carbonized at 400°C for 1 h in an oxygen-deficient environment to obtain biochar; S2. Dissolve FeCl3·6H2O and FeSO4·7H2O in water to prepare iron salt solutions with concentrations of 0.08M and 0.1M respectively, mix the two, and fully immerse the biochar in the mixed iron salt solution. During the stirring process, raise the temperature to 70°C and add sodium hydroxide to adjust the pH to 9 to allow the iron salt to co-precipitate. React for 2 hours. After the reaction, separate, wash and dry the biochar to obtain iron-based biochar.
[0044] Experimental Testing The kitchen waste (organic degradable matter 61.5±3%, paper products 16.8±1%, peel 13.4±1%, plastic 8.3±1%, pH 6.7-7.3, solid content 20±2%, volatile solid 16±2%) was crushed and homogenized, and the inoculated sludge was mixed with the kitchen waste at a mass ratio of 2:1; the mixture was added to the anaerobic tank, which was equipped with a stirrer, a liquid level meter, a temperature sensor, a pressure sensor, a biogas flow meter, a gas analyzer and a pH meter; water was added to dilute the solid content to 10%, the temperature was set to 35°C, and the speed of the stirrer was set to 35rpm; 5 / 1000 of the amount of additional material in the tank was added (or not added), and no feeding or discharging was performed during the experiment. The experiment lasted for 20 days, and the methane production rate and conductivity were measured. Table 1 Effect of different materials on the methane production efficiency of kitchen waste
[0045] In summary, in the process of preparing the modified iron-based biochar composite material, the present invention uses activation treatment to make the biochar have a higher specific surface area and porous structure, improve its adsorption capacity, and can be doped with more iron elements to promote electron transfer and strengthen the electron transfer process between acid-producing bacteria and methanogens; in addition, by coating the surface of the iron-based biochar with a conductive polymer, the overall conductivity and electron transfer efficiency of the material can be significantly improved, the electron transfer network between acid-producing bacteria and methanogens can be improved, and the anaerobic digestion efficiency can be greatly improved, so that the anaerobic system of severely acidified kitchen waste can be quickly restored. Therefore, the present invention effectively overcomes the various shortcomings of the prior art and has a high industrial utilization value.
[0046] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A method for preparing a modified iron-based biochar composite material, characterized in that: The following steps are involved: S1. Using lignocellulose-rich biomass as raw material, the crushed raw material is subjected to low-temperature carbonization treatment in an oxygen-deficient environment to obtain pre-oxidized biochar; S2, activating the pre-oxidized biochar to obtain activated biochar; S3, modifying the iron-based material onto the surface of the activated biochar by a co-precipitation method to obtain iron-based biochar; S4, dissolving the conductive polymer monomer in a solvent, uniformly dispersing the iron-based biochar in the conductive polymer monomer solution, heating the mixed solution to cause an in-situ polymerization reaction, thereby coating the conductive polymer on the surface of the iron-based biochar; S5. After the reaction is completed, the product is separated, washed and dried to obtain the modified iron-based biochar composite material.
2. The method for preparing the modified iron-based biochar composite material according to claim 1, characterized in that: In step S1, the temperature of low-temperature carbonization is between 300 and 500° C., and the time of low-temperature carbonization is between 0.5 and 1 hour.
3. The method for preparing the modified iron-based biochar composite material according to claim 1, characterized in that: In step S2, the activation treatment process includes: mixing the pre-oxidized biochar with an activator solution and heating the solution for a period of time, wherein the activator is selected from phosphoric acid or sulfuric acid, and separating, washing and drying the solution after the reaction to obtain activated biochar.
4. The method for preparing the modified iron-based biochar composite material according to claim 1, characterized in that: In step S3, the co-precipitation modification process includes: dissolving FeCl3·6H2O and FeSO4·7H2O in water to prepare a mixed iron salt solution, fully immersing the activated biochar in the iron salt solution, heating and adjusting the pH during stirring to allow the iron salt to undergo a co-precipitation reaction, and separating, washing, and drying after the reaction to obtain iron-based biochar.
5. The method for preparing the modified iron-based biochar composite material according to claim 1, characterized in that: In step S4, the conductive polymer is selected from at least one of polyaniline, polypyrrole, polythiophene and polyethylenedioxythiophene.
6. The method for preparing the modified iron-based biochar composite material according to claim 1, characterized in that: In step S4, an oxidant is further added during the in-situ polymerization reaction, and the oxidant includes at least one of persulfate and chlorate.
7. The method for preparing the modified iron-based biochar composite material according to claim 3, characterized in that: The temperature of the in-situ polymerization reaction is between 60 and 120° C., and the time of the in-situ polymerization reaction is between 12 and 36 hours.
8. A modified iron-based biochar composite material, characterized in that: The modified iron-based biochar composite material is prepared by the preparation method of any one of claims 1 to 7.
9. Use of the modified iron-based biochar composite material as claimed in claim 8 in the anaerobic engineering of rapid recovery of severely acidified food waste.
10. The use according to claim 9, characterized in that: The specific steps include: (1) A modified iron-based biochar composite material is added into a severely acidified anaerobic tank using a dosing device, wherein the initial start-up amount of the modified iron-based biochar composite material is added at 0.5% of the amount of slurry in the tank; (2) Resume feeding, when the organic load changes from 0kg VS / m 3 Up to 0.5kg VS / m 3 In the stage, the daily feed amount increased by 15% compared with the previous day, and the daily dosage of the modified iron-based biochar composite material was feed amount (t / d)*TS content (%)*5%; (3) When the organic load increases from 0.5 kg VS / m 3 Up to 1.0kg VS / m 3 In the first stage, the daily feed amount increased by 10% compared with the previous day, and the daily dosage of the modified iron-based biochar composite material was feed amount (t / d)*TS content (%)*4%; (4) When the organic load increases from 1.0 kg VS / m 3 Up to 2.0kg VS / m 3 In the first stage, the daily feed amount increased by 5% compared with the previous day, and the daily dosage of the modified iron-based biochar composite material was feed amount (t / d)*TS content (%)*3%; (5) When the organic load increases from 2.0 kg VS / m 3 Up to 3.0kg VS / m 3 In the first stage, the daily feed amount increased by 3% compared with the previous day, and the daily dosage of the modified iron-based biochar composite material was feed amount (t / d)*TS content (%)*2%; (6) When the organic load reaches 3.0 kg VS / m 3 , feed normally every day and stop adding modified iron-based biochar composite materials.
Citation Information
Patent Citations
Method for enhancing anaerobic fermentation to produce biogas by using grafted magnetic biochar
CN116574764A
Preparation method of iron-modified straw biogas residue charcoal, and product and application of iron-modified straw biogas residue charcoal
CN117299756A
Cited By
Porous complex microbial inoculant for promoting nitrate reduction to produce ammonium as well as preparation method and application of porous complex microbial inoculant
CN120290544A
